Depression and anxiety in ovarian cancer: a systematic review and meta-analysis of prevalence rates. Issue 11 (30th November 2015) - Watts, Sam; Prescott, Philip; Mason, Jessica; McLeod, Natalie; Lewith, George
Abstract : Objectives: To systematically review the literature pertaining to the prevalence of depression and anxiety in patients with ovarian cancer as a function of treatment stage. Design: Systematic review and meta-analysis. Participants: 3623 patients with ovarian cancer from primary research investigations. Primary outcome measure: The prevalence of depression and anxiety in patients with ovarian cancer as a function of treatment stage. Results: We identified 24 full journal articles that met the inclusion criteria for entry into the meta-analysis resulting in a pooled sample size of 3623 patients. The meta-analysis of prevalence rates identified pretreatment, on-treatment and post-treatment depression prevalences of 25.34% (CI 22.79% to 28.07%), 22.99% (CI 19.85% to 26.46%) and 12.71% (CI 10.14% to 15.79%), respectively. Pretreatment, on-treatment and post-treatment anxiety prevalences were 19.12% (CI 17.11% to 21.30%), 26.23% (CI 22.30% to 30.56%) and 27.09% (CI 23.10% to 31.49%). Conclusions: Our findings suggest that the prevalence of depression and anxiety in women with ovarian cancer, across the treatment spectrum, is significantly greater than in the healthy female population. With the growing emphasis on improving the management of survivorship and quality of life, we conclude that further research is warranted to ensure psychological distress in ovarian cancer is not underdiagnosed and undertreated.